2011
DOI: 10.1159/000326931
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Bloody Diarrhea as a Side Effect of Mesalamine Treatment of Active Ulcerative Colitis

Abstract: Mesalamine has been used as the first-line therapy for the treatment of ulcerative colitis (UC) because of its efficacy and fewer side effects. However, earlier study showed that mesalamine occasionally causes diarrhea. We are presenting a patient with active UC in whom bloody diarrhea accompanied by abdominal pain and fever occurred and the symptoms were aggravated after administration of mesalamine. In order to clarify the reason of symptoms aggravation, drug lymphocyte stimulation test and rechallenge trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…There have been previous case studies reported of mesalazine worsening diarrhoea in colitis. 29 30 This may represent an allergic response to the drug as we did find an increase in T lymphocytes.…”
Section: Discussionmentioning
confidence: 61%
“…There have been previous case studies reported of mesalazine worsening diarrhoea in colitis. 29 30 This may represent an allergic response to the drug as we did find an increase in T lymphocytes.…”
Section: Discussionmentioning
confidence: 61%
“…There have been previous case studies reporting treatment with mesalazine worsening diarrhoea in colitis. 50,51 This may represent an allergic response to the drug, as we did find an increase in T lymphocytes.…”
Section: Postinfectious Irritable Bowel Syndromementioning
confidence: 55%
“…Colitis-like symptoms had been described in the treatment of ulcerative colitis using sulphasalazine, but also similar presentations had been reported with mesalamine in adults with ulcerative colitis [ 2 , 3 , 4 ]. There are a few reports on mesalamine-related colitis in children with ulcerative colitis [ 8 , 9 ], while it is scarce in children and adults with CD [ 5 ]. In both children and adult cases, abdominal pain, diarrhoea (may be bloody), fever and arthralgias were reported within 24–48 h of starting mesalamine treatment, and these symptoms resolve within 24–48 h of stopping the drug which were similar to our 3 cases.…”
Section: Discussionmentioning
confidence: 99%